(untitled) (Scientific journal of the Fergana State University, 2025)
This article examines the role, opportunities, and impact of virtual laboratories on the effectiveness of biology education. It discusses the limitations of traditional laboratory sessions and how integrating virtual laboratories with modern technologies enhances students’ comprehension of biological sciences. The study reveals that virtual laboratories not only increase students’ scientific interest but also significantly improve the efficiency of educational resources. With the help of virtual laboratories, students can interactively study biological processes, participate in experiments, and overcome potential challenges that may arise in real laboratory conditions.